From protein structure to function via single crystal optical spectroscopy - Ronda, Luca; Bruno, Stefano; Bettati, Stefano; Storici, Paola; Mozzarelli, Andrea (Frontiers in Molecular Biosciences, 2015)
The more than 100.000 protein structures determined by X-ray crystallography provide a wealth of information for the characterization of biological processes at the molecular level. However, several crystallographic “artifacts”, including conformational selection, crystallization conditions and radiation damages, may affect the quality and the interpretation of the electron density map, thus limiting the relevance of structure determinations. Moreover, for most of these structures no functional data have been obtained in the crystalline state, thus posing serious questions on their validity in the inference for protein mechanisms. In order to solve these issues, spectroscopic methods have been applied for the determination of equilibrium and kinetic properties of proteins in the crystalline state. These methods are UV-vis spectrophotometry, spectrofluorimetry, IR, EPR, Raman and resonance Raman spectroscopy. Some of these approaches have been implemented with on-line instruments at X-ray synchrotron beamlines. Here, we provide an overview of investigations predominantly carried out in our laboratory by single crystal polarized absorption UV-vis microspectrophotometry, the most applied technique for the functional characterization of proteins in the crystalline state. Studies on hemoglobins, pyridoxal 5’-phosphate dependent enzymes and green fluorescent protein in the crystalline state have addressed key biological issues, leading to either straightforward structure-function correlations or limitations to structure-based mechanisms.